Pengaruh analisa jabatan dan pengembangan karir terhadap kinerja pegawai PT. Youngan Indo Maju di Tangerang - Fakih, Choerul (Universitas Tangerang Raya, 2024)
Implementation of work Human Resources (HR) is the most important capital in an organization. This research aims to analyze the influence of job analysis and career development on the performance of PT employees. Youngan Indo Maju in Tangerang. This study uses a quantitative approach. The population in this study were 130 employees who worked at PT Youngan Indo Maju. The determination of the number of samples used is a saturated sample. Data analysis in this research was carried out using multiple linear regression analysis. The results of hypothesis testing show that job analysis has a positive and significant effect on employee performance at PT Youngan Indo Maju, career development has a positive and significant effect on employee performance at PT Youngan Indo Maju and position analysis and career development have a positive and significant effect on employee performance at PT Youngan Indo Maju. Suggestions are put forward in this research so that PT Youngan Indo Maju explains the weight of work to employees at PT Youngan Indo Maju well. So that employees know the priority work that must be done